IMPLEMENTASI CATUR PARAMITHA DALAM MENINGKATKAN EMPATI REMAJA: HIDUP SEBAB CINTA ATAU CINTA SEBAB HIDUP? Hidup Sebab Cinta atau Cinta Sebab Hidup? - Sari, Ni Made Nanda; Dewi, Ni Made Mely Fitriana (Sphatika: Jurnal Teologi, 2025)
Catur Paramita is a moral and spiritual teaching in Hinduism that emphasizes four main virtues: Maitri (loving-kindness), Karuna (compassion), Mudita (joy for the happiness of others), and Upeksa (inner peace). These four virtues aim to provide guidance for humans to live a life full of harmony, balance, and peace. As a moral guideline, this teaching not only helps individuals develop noble character but also creates harmonious relationships between humans, nature, and God. Maitri teaches universal love without discrimination, thus encouraging the creation of mutual respect and tolerance. Karuna instills an attitude of compassion, which encourages humans to help others sincerely. Mudita is an attitude of sharing in the success and happiness of others, which helps avoid envy. Upeksa teaches inner peace and the ability to be neutral in facing difficult situations, thus creating peace within oneself. The implementation of this teaching is expected to be able to create a harmonious society, where the values of virtue are the basis for living life. Harmonious relationships with fellow human beings encourage the creation of social peace.  Harmony with nature helps maintain environmental sustainability, while a close relationship with God strengthens an individual's spirituality. The Catur Paramita serve as guidelines for achieving the perfection of life, both in this world and in the afterlife. By applying these teachings, each individual can live a life full of virtue, create inner balance, and contribute to a peaceful and prosperous life for all beings..